PENGARUH AKTIVITAS PENANGAN MATERIAL SECARA MANUAL PEKERJA TERHADAP KELUHAN MUSKULOSKELETAL : TINJAUAN SISTEMATIS - Nada Adinda Irhamna; Chahya Kharin Herbawani (Universitas Pahlawan, 2022)
Manual material handling is an activity that provides easy load transfer in confined or irregular spaces. Based on the Global Burden of Disease (GBD) shows that around 1.71% billion people worldwide have musculoskeletal conditions. This study aims to analyze articles from journals in order to provide reliable information about the effect of manual material handling activities on workers' complaints of musculoskeletal disorders. This study uses a systematic review method by comparing the search results to the literature that has been obtained regarding manual material handling of workers for musculoskeletal complaints. The results obtained were 20 articles which were analyzed in a systematic review. Article published in Elsevier B.V, PubMed, Google Scholar. The inclusion criteria used were having full text, using English and Indonesian, having ISSN/ISBN, and being published in the last 7 years. While the exclusion criteria referred to are research articles that do not meet the sample, are irrelevant, do not comply with the provisions as a predetermined sample, the period of publication of the article before 2014, does not have the complete text, and does not have an ISSN or ISBN. All articles cover manual material handling activities that affect workers' musculoskeletal complaints. Manual material handling consists of pushing, pulling, lowering, lifting, and carrying objects. It can be concluded that proper manual material handling can improve the quality of life for workers.